Ejes estratégicos intersectoriales fundamentados en el paisaje natural y el patrimonio edificado para potenciar el turismo del territorio de Puerto Eten: Intersectoral strategic axes based on the natural landscape and built heritage to promote tourism in the territory of Puerto Eten - Guerrero Samamé, Yvan (2026)
The Peruvian coast has a length of three thousand and eighty kilometers and is traversed transversally by fifty-three rivers that come from the Andes; On the north side of this intertidal zone we find the Lambayecan coastline with one hundred sixty-five kilometers that make up a convergent quadruple boundary space of city, region, water and air; of unique heritage programmatic multiplicity in its dimensions: physical, socio-urban, economic and cultural; here we locate the cities of Pimentel, Puerto Eten, San José and Santa Rosa, which present a series of urban transformations and lack of interest since the boom in agricultural exports. The research studies the richness of cultural, natural and built landscape heritage, compiling relevant and processed information through the juxtaposition of layers or phenomena, proposing articulated actions of its potentialities; The methodology is based on the territorial geography and projective geometry of the territory, finding the main elements of its structure and ordering them in two general logics: the view from the territory, understanding its heritage landscape, and the geographical connectivity, articulating the urban attributes of the Lambayecan coastline. Intersectoral strategies are proposed for the use of heritage, landscape and its tourist potential to develop a stable and permanent territory, differentiated and diverse, substantial and with memory, tangible and flexible; that highlights Puerto Eten as a satellite city of main action, of tourist, patrimonial, cultural, aesthetic and symbolic interest; enhancing its coastal landscape and the interaction of man with its current natural environment.